Characterization of blood-derived exosomal hTERT mRNA as a biomarker for colon cancer and Lynch syndrome - Laish, Ido; Levi, Zohar; Mahajna, Hussein; Albshesh, Ahmad; Horesh, Nir; Katz, Efraim; Feldman, Dan; Shinar, Nadav; Picard, Orit; Yavzori, Miri; Fudim, Ella; Raanani, Pia; et al. (Frontiers in Oncology, 2022)
Background: Human telomerase reverse transcriptase (hTERT)- mRNA was shown to be elevated in exosomes derived from the sera of a variety of hematological and solid cancer patients. We aimed to evaluate its role as a diagnostic marker in patients with newly diagnosed colon cancer and in hereditary syndromes with predisposition to colon cancer. Methods: hTERT -mRNA levels were determined in serum-derived exosomes from 88 patients with colon cancer, 71 Lynch-syndrome carriers with unknown active malignancies and 50 healthy controls. Data, including demographics, background diseases, clinical data regarding tumor characteristics and genetic data, were retrieved data from medical files. Results: Patients with colon cancer had both higher exosomal hTERT mRNA levels and a higher proportion of patients with positive exosomal hTERT mRNA than controls (29.5% vs. 4%, respectively, P values < 0.001). Within the cancer group, patients with a metastatic disease had higher levels of telomerase mRNA than non-metastatic disease patients, and these levels correlated with CEA levels. Likewise, Lynch syndrome carriers had a higher proportion of positive exosomal hTERT mRNA than controls (21.1% vs. 4%, respectively, P value 0.008) but only a trend towards higher exosomal hTERT mRNA levels. Higher telomerase mRNA levels were not correlated with the mutated gene. Conclusions: Exosomal serum hTERT –mRNA levels are associated with metastatic colon cancer and were also demonstrated in a subset of Lynch syndrome carriers. Its significance as a biomarker for developing malignancy should be elucidated.